2011
DOI: 10.1186/1475-2840-10-43
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of N-acetylcysteine as an antiplatelet agent in patients with type-2 diabetes

Abstract: BackgroundPlatelet hyperaggregability is a pro-thrombotic feature of type-2 diabetes, associated with low levels of the antioxidant glutathione (GSH). Clinical delivery of N-acetylcysteine (NAC), a biosynthetic precursor of GSH, may help redress a GSH shortfall in platelets, thereby reducing thrombotic risk in type-2 diabetes patients. We investigated the effect of NAC in vitro, at concentrations attainable with tolerable oral dosing, on platelet GSH concentrations and aggregation propensity in blood from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…15 Several lines of evidence have shown that NAC significantly reduces systemic platelet activation and thrombosis in diabetes, and it can inhibit thrombin-and adenosine diphosphate (ADP)-induced platelet aggregation as well as agonist-induced ectodomain shedding of glycoprotein Ibα (GPIbα) in vitro. 16,17 Given that NAC can act as a safe ROS scavenger, this study examined its effects on the platelet survival and apoptosis during storage of platelet concentrates. Considering NAC as a general scavenger of ROS generated by different sources, to specifically determine the effect of NOX-generated ROS on platelets, we also applied VAS2870 (3-benzyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo[4,5-d]pyrimidine) as a specific inhibitor of these enzymes (mainly NOX1 and NOX2).…”
Section: Discussionmentioning
confidence: 99%
“…15 Several lines of evidence have shown that NAC significantly reduces systemic platelet activation and thrombosis in diabetes, and it can inhibit thrombin-and adenosine diphosphate (ADP)-induced platelet aggregation as well as agonist-induced ectodomain shedding of glycoprotein Ibα (GPIbα) in vitro. 16,17 Given that NAC can act as a safe ROS scavenger, this study examined its effects on the platelet survival and apoptosis during storage of platelet concentrates. Considering NAC as a general scavenger of ROS generated by different sources, to specifically determine the effect of NOX-generated ROS on platelets, we also applied VAS2870 (3-benzyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo[4,5-d]pyrimidine) as a specific inhibitor of these enzymes (mainly NOX1 and NOX2).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes patients, the GSH synthesis itself did not seem to be impaired; however, a lack of the GSH precursors cysteine and glycine was detected. Dietary supplementation of these amino acids or N-acetylcysteine restored GSH synthesis in platelets of diabetic patients and decreased ROS levels and, accordingly, oxidative modifications (228,692). The expression of GR is especially high in islets and inhibition of the enzyme sensitizes b-cells to streptozotocin-induced diabetes (533).…”
Section: Infection Inflammation and Immune Responsementioning
confidence: 99%
“…Cellular Physiology and Biochemistry hyperaggregability in patients with type-2 diabetes [22]. Meanwhile, 3-methyladenine (3-MA), a classic autophagy inhibitor, blocks autophagosome formation by inhibiting type III phosphatidylinositol 3-kinases in platelets [23], and the specific mTOR inhibitor, rapamycin, the most frequently used trigger of autophagy, has been used to inhibit mammalian target of rapamycin (mTOR) function in platelets [24].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%